Factores de riesgo para enfermedad pulmonar obstructiva crónica en adultos del barrio Motupe de la ciudad de Loja - Rodríguez Pardo, Pedro Alexander (2024)
Chronic obstructive pulmonary disease is a prevalent pathology characterized by nonreversible airflow limitation, which causes persistent respiratory symptoms and occurs due to a peculiar inflammatory response; therefore, it is the third cause of death worldwide. The general objective of this research was to determine the risk factors for chronic obstructive pulmonary disease in adults in the Motupe neighborhood of the city of Loja during the period October 2022 to March 2023 and as specific objectives to characterize the population sociodemographic ally, identify the risk factors and develop an educational strategy to prevent the disease. The study was quantitative, descriptive and transversal, in which a survey on sociodemographic information and risk factors was applied to the population consisting of 200 participants. Obtaining results that 42% are between 40 and 49 years old, with the female sex predominating with 56%, the majority are married with 54.5% and 43.5% have a level of primary education. 36.5% consumed cigarettes, 26% were infected by the SARS-CoV-2 virus, 100% were exposed to transport smoke and dust, 79% have been exposed to tobacco smoke and 73% exposed to wood smoke. An educational strategy was developed with the purpose of increasing knowledge about the prevention of this disease. Concluding that the main risk factors found to develop the pathology were exposure to smoke generated by transportation, tobacco, firewood and dust, therefore, it is necessary to apply preventive measures in the community based on the proposals of the educational strategy carried ouT